Access to health care for transvestites and transgender women in Brazil (Research, Society and Development, 2022)
Transvestites and transgender women suffer social exclusion, have a high burden of disease and low life expectancy. This work is an integrative review with the objective of describing the Access of these people to healthcare in Brazil. We searched the SCIELO, LILACS, VHL and PUBMED platforms for the following descriptors: Sexual and Gender Minorities; Transgender Persons; Transvestism; Health Services Accessibility; Therapeutics; Unified Health System; Health Services for Transgender Persons. We selected 39 articles with the following categories: Access to the Unified Health System (SUS) and social rights, Acquired Human Immunodeficiency Virus (HIV) and HIV pre-exposure prophylaxis (PreP), perception of health professionals about transsexuality, use of hormones, feminization strategies, social name and consumption of alcohol and drugs. The non-use of the social name in the SUS, the inadequate consumption of hormones and liquid silicone reveal the little Access to the SUS. Alcohol and drug abuse, prostitution, low income and little schooling are important factors for a poor quality of life. There is a high prevalence of HIV and viral load suppression is low in this population where a minority use Prep. Primary health care has not fulfilled its role as a gateway and care coordinator in the SUS. The number of surgeries performed in the SUS transsexualization process is low and economic and people management investments are needed to improve this situation.